Roadmap Design for Competency Requirements in Mathematics for the Electrical Engineering Curriculum at Universitas Negeri Padang - rezki, indra Kurniawan; Nizwardi Julinus; Giatman; Rijal Abdullah; Nurhasan Syah; Ridwan; Arnellis (Rangkiang Mathematics Journal, 2024)
Field observations reveal that students in the Electrical Engineering program at Universitas Negeri Padang (UNP) struggle to master the standard mathematical content required, impacting their ability to comprehend advanced course materials. The current applied mathematics curriculum does not sufficiently support students in independently discovering concepts essential for engineering competencies. This study aims to establish a standardized competency design for applied mathematics that aligns with the mathematical requirements of the electrical engineering curriculum, thereby simplifying the learning of advanced courses. Utilizing a qualitative descriptive approach, this research gathers insights from alums, students, and expert lecturers through interviews. The findings identify seven essential mathematical topics that form the foundation of cognitive knowledge. These fundamental skills are crucial in achieving competencies that significantly contributing to success in advanced courses within the UNP Electrical Engineering program. The seven core topics include calculus, geometric and trigonometric functions, mathematical modeling and logic, discrete mathematics, integrals and differential equations, complex variables, and linear algebra